2019
DOI: 10.3390/cancers11070996
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Glioblastoma with Bortezomib Potentiates Natural Killer Cell Cytotoxicity through TRAIL/DR5 Mediated Apoptosis and Prolongs Animal Survival

Abstract: Background: Natural killer (NK) cells are potential effectors in anti-cancer immunotherapy; however only a subset potently kills cancer cells. Here, we examined whether pretreatment of glioblastoma (GBM) with the proteasome inhibitor, bortezomib (BTZ), might sensitize tumour cells to NK cell lysis by inducing stress antigens recognized by NK-activating receptors. Methods: Combination immunotherapy of NK cells with BTZ was studied in vitro against GBM cells and in a GBM-bearing mouse model. Tumour cells were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 64 publications
0
37
0
Order By: Relevance
“…BTZ-induced tumour death generates immunogenic antigens and sensitizes to dendritic cell immunotherapy. 24,31,32 Thus, we investigated the patients' T cell activation and maturation status in blood and cytokines circulating in their plasma at baseline, after exposure to BTZ only (within the first 8 hours after administration), BTZ + TMZ (on days 4-7) and during the 3 weeks recovery period (days 11, 15, and 22) in cycle 1. We also investigated responses to stimulation with PMA/ionomycin or autologous tumour cells ex vivo of patients' PBMCs obtained at baseline (BTZ naïve) versus those obtained during recovery (day 22-56) after initial exposure to BTZ + TMZ.…”
Section: Immunological Mechanisms Of Patients With Positive Clinicamentioning
confidence: 99%
See 1 more Smart Citation
“…BTZ-induced tumour death generates immunogenic antigens and sensitizes to dendritic cell immunotherapy. 24,31,32 Thus, we investigated the patients' T cell activation and maturation status in blood and cytokines circulating in their plasma at baseline, after exposure to BTZ only (within the first 8 hours after administration), BTZ + TMZ (on days 4-7) and during the 3 weeks recovery period (days 11, 15, and 22) in cycle 1. We also investigated responses to stimulation with PMA/ionomycin or autologous tumour cells ex vivo of patients' PBMCs obtained at baseline (BTZ naïve) versus those obtained during recovery (day 22-56) after initial exposure to BTZ + TMZ.…”
Section: Immunological Mechanisms Of Patients With Positive Clinicamentioning
confidence: 99%
“…Indeed, we demonstrated that natural killer (NK) cells treated with BTZ exhibited more mature, activated and cytotoxic CD57 + CD16 dim CD69 + phenotype, and that efficacy of combination treatment of GBM cells with BTZ + NK cells in vitro and in vivo was augmented by tumor necrosis factor related ligand (TRAIL)-receptor interactions, as well as tumor expression of stress-ligands recognized by activating NKG2D receptor. 24 Sequential combination of BTZ 48 hours before TMZ 164 mg/m 2 treatment, depleted MGMT mRNA in vivo, attenuated tumor growth and significantly prolonged animal survival. 22 Thus, this phase IB of our BORTEM-17 clinical trial (NCT03643549) was launched to investigate whether pretreatment of recurrent GBM patients with BTZ 1.3 mg/m 2 on days 1, 4, and 7, to deplete MGMT levels 48 hours before TMZ, commencing on days 3 to 7 every 4th week, might sensitize MGMT unmethylated GBM to TMZ chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…GB stem-like cells are more susceptible to lysis by NK cells than differentiated GB cells [277]. In animal models, pretreatment of GB with bortezomib has been shown to promote NK cell cytotoxicity and to inhibit tumor growth ultimately leading to prolonged survival [278]. Varicella zoster virus (VZV) is the only virus with negative correlation with GB [169,279].…”
Section: Nk Cells In Solid Tumorsmentioning
confidence: 99%
“…Previous studies have shown that bortezomib disrupts multiple downstream signalling pathways, such as the NF‐κB signalling pathway and ubiquitin‐proteasome pathway, and has an important role in the regulation of cell cycle, mitosis, cell viability, proliferation and apoptosis in glioblastoma cells . It also blocks autophagy flux mediated by the 26S proteasome, thereby inhibiting the elimination of damaged organelles, and inhibits the proliferation of glioblastoma. Polo‐like kinase 4 (PLK4) is critical for embryonic development and cell cycle control.…”
Section: Introductionmentioning
confidence: 99%